Teaching materials for neighbouring language teaching at school. A German-Dutch comparison - Boonen, Ute K.; Jentges, Sabine; Konrad, Tina (Glottodidactica, 2018)
This paper discusses the differences between teaching Dutch in Germany and German in the Netherlands, while considering the challenges teachers are confronted with, e.g. the lack of appropriate textbooks. In particular, the composition and method of some textbooks for Dutch and German are presented and evaluated with regard to their practicality in the classroom. It is striking that textbooks for German are written in Dutch, and that pupils even have to work out tasks in Dutch and not in the target language, while there is merely one textbook in Germany for school-based teaching, lacking a consideration of school types, age groups, and prior knowledge. Even though the conditions of neighbouring language teaching are particularly diverse, teachers on both sides are in urgent need of more innovative and improved teaching material which ensures that pupils are able to develop and improve their language skills, as well as their intercultural competences.